PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL DAN STRUKTUR MODAL TERHADAP INCOME SMOOTHING - Elisabeth Angelina; Munandar, Agus (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
In general, the company's performance is reflected in its financial statements. To provide good company performance, managers must make policies and decisions on choosing accounting methods to finance company operations either by using debt or using equity in acquiring assets to obtain stable profits, not too high, not too low. Based on this basis, this study examines profitability, managerial ownership, and capital structure that affect income smoothing. The research data was taken on the IDX website using the transportation and logistics sector as research subjects for 2018-2021. Based on the results of panel data regression analysis, the variables of profitability, managerial ownership and capital structure have an effect on income smoothing both simultaneously and separately.